Nomogram of intra-abdominal infection after surgery in patients with gastric cancer: A retrospective study - Zhang, Yue; Wang, Zhengfei; Basharat, Zarrin; Hu, Mengjun; Hong, Wandong; Chen, Xiangjian (Frontiers in Oncology, 2022)
Background: At present, surgical resection is still the main way to treat gastric cancer. Postoperative complications such as IAI (intra-abdominal infection) are important problems that clinical front-line workers should pay special attention to. This article was to build and validate a RF (regression function) model of IAI. Furthermore, it also analyzed the prognosis in patients with IAI after surgery for stomach cancer. Methods: The data of this study was divided into two parts, training data set and validation data set respectively. The training data for this article were from the patients treated surgically with gastric cancer in the First Affiliated Hospital of Wenzhou Medical University from December 2015 to February 2017. In the training data set, we examined the morbidity, etiological characteristics, and prognosis of IAI. Univariate analysis and a multivariate logistic regression analysis were used to screen risk factors, establish a RF model and create a nomogram. Data from January to March 2021 were used to validate the accuracy of the RF model. Results: The incidence of IAI was 7.2%. The independent risk factors for IAI were hypertension (Odds Ratio [OR] = 3.408, P = 0.001), the history of abdominal surgery (OR = 2.609, P = 0.041), combined organ excision (OR = 4.123, P = 0.010), and operation time ≥240 min (OR = 3.091, P = 0.005). In the training data set and validation data set, the area under ROC curve of IAI predicted by RF model is 0.745±0.048 (P<0.001) and 0.736±0.069 (P=0.003), respectively. In addition, IAI significantly extended the length of hospital stay, but had little impact on survival. Conclusions: Patients with hypertension, combined organ excision, the history of abdominal surgery and a surgical duration of 240 min or more are prone to IAI and the RF model may help to identify them.